Broilers fed a low protein diet supplemented with synthetic amino acids maintained growth performance and retained intestinal integrity while reducing nitrogen excretion when raised under poor sanitary conditions - Macelline, Shemil P. (Poult Sci, 2019)
The present study investigated the effects of supplementing a low protein (LP) diet supplemented with key essential amino acids (AA) to broilers on growth performance, intestinal tract function, blood metabolites, and nitrogen excretion when the animals were maintained under various sanitary conditions for 35 D after hatching. Three hundred eighty-four one-day-old male broilers (Ross 308) were randomly allotted to groups that received one of 6 dietary treatments in a 2 × 3 factorial arrangement (i.e., 2 environmental conditions and 3 dietary treatments) to give 8 replicates per treatment. Broilers were challenged with 2 environmental conditions (sanitary vs. poor sanitary). The dietary treatments were (1) high protein (HP) diet, (2) LP diet, and (3) LP diet with synthetic key essential AA (LPA): the LP diet was supplemented with synthetic AA up to the required levels for broilers. On day 14, birds consumed the LP diet impaired growth performance compared with those fed the HP diet, while the average daily weight gain-to-feed conversion ratio of birds fed the LPA diet improved to the level of birds fed the HP diet under poor sanitary conditions (P < 0.05). Broilers raised under poor sanitary conditions and fed the LP diet displayed higher (P < 0.05) zonula occludens (ZO-1) expression on day 14 than broilers fed either the HP or LPA diet. Under sanitary conditions, birds fed HP and LPA diets showed higher villus height and crypt depth compared with those of broilers fed the LP diet on day 35. Moreover, broilers raised in the poor sanitary environment had higher (P < 0.05) serum endotoxins than those raised in the sanitary environment. Broilers fed the LPA diet showed reduced (P < 0.05) nitrogen excretion on days 14 and 35 compared with those fed the LP and HP diets independent of the environment. In conclusion, the LPA diet did not impair growth performance under poor sanitary conditions for 14 D after hatch while resulting in lower nitrogen excretion in any environment conditions throughout the experiment.